ESR essentials - lung cancer screening with low-dose CT: practice recommendations by the European Society of Thoracic Imaging - Revel, Marie-Pierre; Biederer, Jürgen; Nair, Arjun; Silva, Mario; Jacobs, Colin; Snoeckx, Annemiek; Prokop, Mathias; Prosch, Helmut; Parkar, Anagha P.; Frauenfelder, Thomas; Larici, Anna Rita (European radiology, 2025)
Low-dose CT screening for lung cancer reduces the risk of death from lung cancer by at least 21% in high-risk participants and should be offered to people aged between 50 and 75 with at least 20 pack-years of smoking. Iterative reconstruction or deep learning algorithms should be used to keep the effective dose below 1 mSv. Deep learning algorithms are required to facilitate the detection of nodules and the measurement of their volumetric growth. Only large solid nodules larger than 500 mm3 or those with spiculations, bubble-like lucencies, or pleural indentation and complex cysts should be investigated further. Short-term follow-up at 3 or 6 months is required for solid nodules of 100 to 500 mm3. A watchful waiting approach is recommended for most subsolid nodules, to limit the risk of overtreatment. Finally, the description of additional findings must be limited if LCS is to be cost-effective.